SAT0015 Identification and characterisationof high molecular weight hmgb1 protein complexes: implications for stress response, innate immunity and autoimmune disease. (12th June 2018) - Willis, W.; Wang, L.; Wada, T.T.; Garder, M.; Abdouni, O.; Valiente, G.; Agarwal, S.; Freitas, M.A.; Wu, L.-C.; Jarjour, W.N.
Abstract : Background: High mobility group box one protein (HMGB1) is a chromatin associated protein, which in response to stress or injury translocates from the nucleus to the extracellular milieu to serve as an alarmin. HMGB1 has a remarkable ability to form complexes with proinflammatory molecules. This is underscored by the emerging role of HMGB1 in rheumatic diseases such as systemic lupus erythematosus (SLE), where the presence of HMGB1 in complex with endogenous nuclear components such as dsDNA or nucleosomes was shown to play an important role in breaking immune tolerance against nuclear antigens. 1 Although the function of HMGB1 is in-part determined by the complexes it forms with other molecules, structural modifications in the HMGB1 polypeptide that may regulate complex formation have not been described. Objectives: In this study we investigated the presence of HMGB1 in large protein complexes (HMGB1c) in human plasma. The objectives of this study were to isolate and characterise HMGB1c as well as to determine the mechanism of its formation. Methods: We examined the presence of HMGB1c in plasma from SLE patients and healthy controls using semi-denaturating detergent agarose gel electrophoresis (SDD-AGE) folowed by Western blot analysis. Immunoblotting, coimmunoprecipitation, confocal microscopy, and mass spectrometry were used to detect and characterise novel high molecular weight HMGB1 variants in vitro as well as in cell lines and primary cells. Mechanisms of HMGB1c formation were delineated via mass spectrometry, RNA interference, and in vitro enzyme reactions. Results: In this study we note the presence of high molecular weight, denaturing resistant HMGB1 protein complexes (HMGB1c) that were present in the plasma of SLE patients and to a much lesser extent, healthy subjects. Similarly, HMGB1c were induced when cells were incubated with endotoxin or alum. Here we report that HMGB1c formation is catalysed by the calcium-activated protein crosslinking enzyme transglutaminase-2 (TG2). HMGB1-TG2 interaction was demonstrated via coimmunoprecipitation as well as by confocal microscopy after co-transfection of cells with plasmids encoding fluorescent-tagged HMGB1 and TG2 constructs. Moreover, HMGB1c formation was suppressed in cells by TG2 siRNA. Crosslink site mapping and analysis by mass spectrometry revealed that HMGB1 can be crosslinked to TG2 as well as a number of additional proteins, including human autoantigens. Conclusions: TG2 catalyses the formation of high molecular weight HMGB1 protein complexes. Given the immunoadjuvant properties of HMGB1 and the implication of TG2-mediated protein complex formation as a possible mechanism by which immune tolerance can be broken to self-molecules, 2 these findings have significant physiological implications for the role of HMGB1 in cellular stress responses and innate immunity in lupus. References: [1] Urbonaviciute V, Furnrohr BG, Meister S, Munoz L, Heyder P, De MF, et al. Induction of inflammatory and immune responses by HMGB1-nucleosome complexes: implications for the pathogenesis of SLE. J Exp Med2008;205:3007–3018. [2] Dieterich W, Ehnis T, Bauer M, Donner P, Volta U, Riecken EO, et al. Identification of tissue transglutaminase as the autoantigen of celiac disease. Nat Med1997;3:797–801. Disclosure of Interest: None declared